Endoscopy - Amornyotin, Somchai (IntechOpen, 2013)
Endoscopy has had a major impact in the development of modern medicine and other medical specialties. The field of endoscopic procedure has developed over the last decade. By using different data it provided a better understanding of pathogenic mechanisms, described new entities and used for early detection, diagnostic procedures and therapeutic procedures. The advantages of many technical advances and modern endoscopic equipments, endoscopy has had a developed spectacularly. Consequently, endoscopy has surpassed its function as an examination tool and it became a rapid and efficient therapeutic tool of various organs including gastrointestinal tract, head and neck, respiratory tract and others. The efficacy and usefulness of endoscopy has yet been established.